Interest of the sentinel node in the case of infiltrating T1 luminal a breast carcinoma: retrospective study at the gynaecology department of the Francois Quesnay Mante-La-Jolie hospital, France - Raou, Kassé; Charles, Kakou; Kinifo, Yeo; Chrisostome, Boussou; Alexis, Yao; Issa, Ouattara; Serge, Boni; Joseph, Bakar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: During these last twenty years, technic of sentinel lymph node (SLN) stayed the gold standard for axillary exploration, an alternative to axillary dissection in the surgical management of breast cancer. Objective of the study was to make an inventory of the technic of the sentinel lymph node technique in forms T1 Luminal A breast cancers. Methods: It was a retrospective, descriptive and analytical study over a period of one year (March 2022 to March 2023) in the Gynecology department, François Quesnay hospital, in Mantes-La Jolie (France). Out of 103 files studied, we included 50 patients who had undergone sentinel lymph node excision for T1 luminal A breast cancers with non-palpable and non-detectable lymph nodes on imaging. The parameters studied were epidemiological data, clinical data and paraclinical data. The Chi2 test (α=5%) made it possible to compare the groups (p<0.05 and CI=95%). Results: The sentinel lymph node excision rate was 48.5%. The median age was 59 years. The epidemiological profile was as follows: Postmenopausal patients (70%), with family history of breast cancer (36%). The circumstances of discovery were: The perception of a breast mass (94%) and the screening examination (34%). The histological lesions were infiltrating ductal carcinomas in 94% of cases and 60% located in the right breast. There were 12 (24%) lymph node metastatic lesions, including 5 macrometastases and 7 micrometastases. There was no link between metastatic involvement of sentinel lymph nodes and age, menopause, family history of breast cancer, concept of screening, histological type. The Chi square was respectively 0; 1.34; 0.05; 0.41; 1.01. There was a link when the cancer was located in the right breast (chi2=10.52 and p=0.001), [CI = (12.16-35.84)]. Conclusions: There was no link between metastatic involvement of sentinel lymph nodes and luminal histological type A, T1. Furthermore, there was a link between metastatic involvement of the sentinel lymph node and the right-sided location of breast cancer. Is this linked to the predominance of cancer in the right breast?